Effects of Experimental Releases of Oil and Dispersed Oil on Arctic Nearshore Macrobenthos. III. Macroalgae - Cross, William E.; Wilce, Robert T.; Fabijan, Michael F. (ARCTIC, 1987)
An experimental subsurface release of chemically dispersed oil at Cape Hatt, northern Baffin Island, resulted in short-term relatively high oil concentrations in the water of two adjacent bays. Untreated oil released onto the surface of the third bay could not be detected in the water below a depth of 1 m. Both releases, however, resulted in measurable contamination of sediments in shallow water. Macroalgae at 3 m depth were sampled by a diver-operated airlift sampler in three treatment bays and in a fourth (reference) bay during the open water seasons of 1980-83 (two pre-spill and four post-spill sampling periods). Biomass, number of species and reproductive condition of the dominant understory algae at 3 m depth did not seem to be adversely affected wither by oil in subtidal sediments or by chemically dispersed oil in the water column. No oil effects were detected in data on the biomasses of total algae or of two of the three species analyzed (Stictyosiphon tortilis and Pilayella littoralis). In the third species, Dictyosiphon foeniculaceus, growth increased in the year following the oil release, either stimulated by low levels of oil in sediments or through natural annual variability. The lack of major effects on macroalgae may have been partly attributable to the lack of effects on herbivores and the vegetative mode of reproduction in the dominant macroalgal species.Key words: arctic macroalgae, oil effects, dispersed oil effects, experimental oil releases, Baffin Island, macrobenthos, Stictyosiphon tortilis, Pilayella littoralis, Dictyosiphon foeniculaceus Mots clés: macro-algues arctiques, effets dus au pétrole, effets dus au pétrole dispersé, déversements expérimentaux de pétrole, île Baffin, macrobenthos, Stictyosiphon tortilis, Pilayella littoralis, Dictyosiphon foeniculaceus